Revision of species Plagiolophus sulcatus Beurlen, 1939 (Decapoda, Brachyura) from the Oligocene of Hungary and Slovenia - Matúš HYŽNÝ; Rok GAŠPARIČ; Alfréd DULAI (Geologija, 2020)
The crab species Plagiolophus sulcatus Beurlen, 1939 from the Oligocene (Rupelian) Kiscell Clay of Hungary is revised and its holotype is reillustrated for the first time since its original publication. Material from the upper Oligocene (Chattian) of Trbovlje (Slovenia) is here considered conspecific with P. sulcatus. Attribution of this species to the genus Glyphithyreus, as proposed by Hiroaki Karasawa and Carrie Schweitzer in 2004, is confirmed. Glypthithyreus sulcatus differs from congeners in possessing protogastric regions that are subtriangular in outline and in having fewer and coarser tubercles on elevated carapace regions.